2005
DOI: 10.1186/1472-6920-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Feedback on video recorded consultations in medical teaching: why students loathe and love it – a focus-group based qualitative study

Abstract: Background: Feedback on videotaped consultations is a useful way to enhance consultation skills among medical students. The method is becoming increasingly common, but is still not widely implemented in medical education. One obstacle might be that many students seem to consider this educational approach a stressful experience and are reluctant to participate. In order to improve the process and make it more acceptable to the participants, we wanted to identify possible problems experienced by students when ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 13 publications
6
58
0
6
Order By: Relevance
“…Consistent with previous studies (Del Mar & Isaacs, 1992;Nilsen & Baerheim, 2005;Yoo et al, 2009), a majority of students agreed that the self-assessment exercise was beneficial in the development of their communication skills.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Consistent with previous studies (Del Mar & Isaacs, 1992;Nilsen & Baerheim, 2005;Yoo et al, 2009), a majority of students agreed that the self-assessment exercise was beneficial in the development of their communication skills.…”
Section: Discussionsupporting
confidence: 73%
“…Underestimations of eye contact may have been related to perceived nervousness or referring to the prescription blank for counseling information. Several studies have described the varying degrees of anxiety that are associated with the anticipation of being video-recorded during simulated patient interactions (Del Mar & Isaacs, 1992;Lindon-Morris & Laidlaw, 2014;Nilsen & Baerheim, 2005). Del Mar and Isaacs (1992) reported that approximately 25% of students whose consultation skills were video-recorded felt intimidated by the camera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several students reported feeling nervous at the thought of their performance being recorded and evaluated. However, as predicted by Nilsen and Baerheim (2005), initial anxiety was overtaken by increased comfort with the process used to debrief and facilitate the discussion. We discuss in the recommendations below how feelings of anxiety experienced by student coaches were mitigated using a variety of instructional strategies.…”
Section: Reflections On the 360° Review Processmentioning
confidence: 96%
“…Likewise, Roter and colleagues (2004) found in their study of communication training of medical residents that instant video feedback following a role play enabled greater learning and predicted significantly improved levels of empathy, reduced verbal dominance and use of open questions. A later investigation using focus group methodology by Nilsen and Baerheim (2005) showed medical students grew in self-esteem and confidence following video feedback after simulated consultations, despite their apprehension about the video feedback process at the beginning of their course of study.…”
Section: Video Replay Feedback Sessionmentioning
confidence: 99%